Trends in teenage pregnancy in England and Wales: how can we explain them? - Wellings, K (1999)
Teenage pregnancy is associated with adverse social and physical outcomes for both mother and child. We drew on various sources--birth and abortion statistics from the Office for National Statistics, data from the National Survey of Sexual Attitudes and Lifestyles, and routinely collected data from family planning clinics--to identify trends in England and Wales and their possible determinants. The rate of teenage sexual activity has increased steadily and consistently over the past four decades, whilst the rate of teenage fertility has shown greater variation. When the teenage fertility rate is calculated against the denominator of sexually active women, rather than the total sample of teenage women, the underlying trend in teenage fertility over the past four decades has been downwards, though not consistently so. Fluctuations in the teenage fertility rate seem to track intervention-related factors such as access to, and use of, contraceptive services and the general climate surrounding the sexual health of young people.